Conceptualizing Party Financing Legislation in Malaysia: Between Normative and Reality - Azmil Tayeb; Dineskumar Ragu (Asia-Pacific Journal of Elections and Democracy, 2021)
How political parties finance their operations is not well regulated in Malaysia. There is no specific law that oversees the myriad ways political parties raise funds and to what purpose they are used. This stands in contrast to neighboring Indonesia and the Philippines, where there are laws that regulate party financing. As a result, corruption in the name of political donations is rampant in Malaysia, the infamous one being the 1MDB scandal that presently ensnares the former Prime Minister, Najib Razak. However, absence of a law that regulates party financing and the inability of the current government to enact one does not mean that Malaysia should sideline the importance of keeping political parties in line with democratic norms. In this article we argue for a normative party financing model based on five criteria if Malaysia is to promulgate a legislation to regulate political parties’ finances. We suggest the proposed legislation should incorporate reporting mechanism that enforces transparency and accountability; level playing field that allows common people and smaller parties to have a stronger voice in politics; reducing patronage politics; easing ethnoreligious tensions; and establishing clear separation between business and politics. We interviewed numerous party representatives, academics, and Election Commission official to solicit their inputs on the substance and viability of this proposed party funding legislation based on the abovementioned five criteria. The article ends with a set of recommendations on the ways to move forward with this proposed legislation or its iterations, both at the federal and state levels.